Konsep Kafir Dalam Tiga Agama Besar - Abdullah Muslich Rizal Maulana; Fauzan Adzima; Muhammad Hudaya (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2020)
The Controversy of the concept of Kafir -excluding a religious group from one- is basically related to the doctrine of Religious Pluralism. Religious Pluralism relativized and nullified religious values so, by consequence, it reduced the theological concepts that existed in religions. In fact, every religion owns its own concepts regarding ‘The Other’ affirmed as its fundamental teachings. This paper will find at least two things: The concept and term of Kafir are already full-fledged in Islam, which was curtailed in the process as an impact of Religious Pluralism. Furthermore, Religious Pluralism is potentially reducing argumentations of the concepts owned in three Major Religions: Islam, Judaism, and Christianity.